2009
DOI: 10.1063/1.3094751
|View full text |Cite
|
Sign up to set email alerts
|

Electronic coupling of colloidal CdSe nanocrystals monitored by thin-film positron-electron momentum density methods

Abstract: The effect of temperature controlled annealing on the confined valence electron states in CdSe nanocrystal arrays, deposited as thin films, was studied using two-dimensional angular correlation of annihilation radiation. A reduction in the intensity by ϳ35% was observed in a feature of the positron annihilation spectrum upon removal of the pyridine capping molecules above 200°C in a vacuum. This reduction is explained by an increased electronic interaction of the valence orbitals of neighboring nanocrystals, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…In-situ electron microscopy on monolayers of PbSe NCs [18] showed that the removal of ligand molecules by a gentle heating in a vacuum at moderate temperatures is accompanied by the formation of interfaces between the NCs. We demonstrated in temperature-dependent 2D-ACAR experiments [19] that depth-profiling positron-electron momentum density methods may reveal the coupling of valence electrons of neighboring CdSe NCs due to the interface formation ( Fig. 1), which will affect the transport of holes.…”
mentioning
confidence: 98%
“…In-situ electron microscopy on monolayers of PbSe NCs [18] showed that the removal of ligand molecules by a gentle heating in a vacuum at moderate temperatures is accompanied by the formation of interfaces between the NCs. We demonstrated in temperature-dependent 2D-ACAR experiments [19] that depth-profiling positron-electron momentum density methods may reveal the coupling of valence electrons of neighboring CdSe NCs due to the interface formation ( Fig. 1), which will affect the transport of holes.…”
mentioning
confidence: 98%
“…Recent proposals for improved dye-sensitized solar cells [25,26] involve replacing the liquid dye by nanoparticles attached to a substrate and exploiting FRET to achieve efficient energy transfer [27]. One candidate material is a mixture of QDs and the protein bacteriorhodopsin (bR) [28], [29], [30].…”
Section: Application: Quantum Dots and Bacteriorhodopsinmentioning
confidence: 99%
“…15 Furthermore, in ligand-exchange studies, it was demonstrated that short-chain diamines effectively strip lead oleate from (100) surfaces of the PbSe QDs. 23,31 The ligand replacement remains incomplete, particularly for the PbSe {100}-facets, which remain partially bare.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Clearly, the development of methods to investigate and monitor surfaces of PbSe QDs embedded in a sub-surface layer in such devices is of crucial importance. In this regard, positron annihilation spectroscopy (PAS) offers unique advantages over XAS, OAS and XPS, since it combines a high sensitivity to selectively probe surfaces of nanoparticles [14][15][16] with an established capacity for depth-profiling of films in the range of ~10 nm to a few m. [17][18][19] These unique merits are highly important in studies of photovoltaic devices, where charge carrier separation requires the formation of a p-n junction, 8 and PAS can probe the involved light absorbing and charge separation layers independently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation